P(OEt)3-Mediated Formal S–H Insertion: Reductive Couplings of Isatins with Thiols to Generate 3-Sulfenylated Oxindoles - Huang, Tiao; Liu, Li; Wang, Qinghe; Kong, Dulin; Wu, Mingshu (Synthesis, 2020)
A new P(OEt)3-mediated formal S–H bond-insertion reaction of isatins into thiols for the synthesis of valuable 3-sulfenylation oxindoles has been developed. This approach takes advantage of the unique reactivity of Kukhtin–Ramirez adducts to allow direct reductive S–H functionalization with commercially available and bench-stable starting materials.
Keywords: triethyl phosphite; S–H bond insertion; carbenoids; 3-sulfenylation oxindoles; isatins